PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING PADA MATERI MATRIKS UNTUK PESERTA DIDIK KELAS XI SMA/MA - Lialy Sarti (Departemen Matematika, 2021)
The purpose of this research is to develop student worksheets on the matrix that is valid and practical using the discovery learning model. This is because the student worksheets used in the learning process are still not able to facilitate students to be actively involved in discovering a concept or principle to construct their knowledge. The type of this research is Research and Development (R&D). This research used the Plomp model which consists of three phases, namely preliminary research, development or prototyping phase, and assessment phase. The research data were collected by using a questionnaire, interview, and observation. The data from the questionnaire were analyzed by using descriptive techniques, while the data from observations and interviews were analyzed by using descriptive statistics. The results of this research are (1) the student worksheets developed has a very valid category with a validity value of 82.78%, (2) the student worksheets can be used easily by students in the learning process with a practicality value of 88.47% with very practical category. Based on the research results, it can be concluded that the developed student worksheets can be applied in mathematics learning in schools. Keywords – Student Worksheet, Discovery Learning, Matrix, Plomp